Systematic Literature Review : Peran Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Guru - Hopipah Yuniana Diba (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to conduct a literature review related to the role of principal supervision in improving teacher performance. Through a structured literature review of 15 articles, this study identified various supervision strategies implemented by principals and their impact on improving teacher performance. The results of the study indicate that effective supervision can improve work motivation, teaching skills, and educational quality. Key factors such as communication, constructive feedback, and professional training contribute to successful supervision. The results of this review indicate that effective principal supervision can improve work motivation, teaching skills, and improve the quality of education in schools. Factors such as good communication, providing constructive feedback, and empowering teachers through professional training are key elements in successful supervision. This study also identified challenges in implementing supervision, such as limited time and resources that affect the effectiveness of principal supervision. This research is expected to provide insights for principals and policymakers to design more effective supervision strategies to improve teacher performance.